The Effect of Transparency and Sharia Services on Customer Satisfaction in Murabahah Financing Services - Khair, Abdul; Muslim, Muhammad; Fahreza, M. Rizky; Ferdiansyah, Ferdiansyah; Syahputra, Deni (Al-Sharf: Jurnal Ekonomi Islam, 2025)
This study aims to determine the effect of transparency and sharia services on customer satisfaction with murabahah financing services at BSI KCP Stabat. The background of this study is based on the importance of information transparency and services that reflect Islamic values in enhancing customer trust and comfort in transactions. This study employs a quantitative method with an associative relationship type, and data was collected through the distribution of questionnaires to 60 respondents who are murabahah financing customers. The sampling technique used was purposive sampling. Data were analysed using SPSS version 21 through the stages of validity testing, reliability testing, classical assumptions, multiple linear regression, and hypothesis testing. The results of the study indicate that both independent variables, namely transparency and sharia services, have a significant effect on customer satisfaction. The coefficient of determination (R²) value of 0.871 indicates that 87.1% of customer satisfaction can be explained by transparency and sharia services. The t-test also shows that each variable has an individual effect, with transparency having a significance value of 0.006 and sharia services having a significance value of 0.000. It can be concluded that the higher the level of information disclosure and the better the sharia services provided, the higher the customer satisfaction. This finding emphasizes the importance of improving transparency and the quality of services based on Islamic values as a strategy to maintain customer loyalty.